Continuation versus discontinuation of first-line chemotherapy in patients with metastatic squamous cell oesophageal cancer: A randomised phase II trial (E-DIS). (April 2019) - Adenis, A.; Bennouna, J.; Etienne, P.L.; Bogart, E.; Francois, E.; Galais, M.P.; Ben Abdelghani, M.; Michel, P.; Metges, J.P.; Dahan, L.; Conroy, T.; Ghiringhelli, F.; et al.
Abstract: Purpose: The role of chemotherapy has not been established in the treatment of metastatic squamous cell oesophageal cancer (mESCC). Patients and methods: E-DIS is a discontinuation trial, aimed at estimating efficacy, quality of life and safety of chemotherapy continuation (CT-CONT) in patients with mESCC who are free from progression after a selection phase of chemotherapy. The primary end-point was overall survival. Results: Sixty-seven patients were randomised. The 9-month survival rate was 50% (85% confidence interval [CI]: 37–62%) and 48% (85% CI: 35–60%) in the CT-CONT arm and in the chemotherapy discontinuation (CT-DISC) arm, respectively. The time until definitive deterioration of the global health status (European Organisation for Research and Treatment of Cancer [EORTC] core quality of life questionnaire) was 6.6 months (95% CI: 3.3–12.4) for the CT-CONT arm and 4.2 months (95% CI: 2.9–6.3) for the CT-DISC arm, with a hazard ratio (HRCT-DISC/CT-CONT ) = 1.44 (95% CI: 0.82–2.53). We observed a beneficial trend in favour of CT-CONT (HR > 1) for most dimensions, including an improvement for three dimensions (dysphagia, eating and oesophageal pain) of the EORTC Oesophageal Cancer Module QLQ-OES18. Conclusion: CT-CONT provides an overall survival rate that is similar to CT-DISC. E-DIS trial provides valuable data to support shared decision-making between physicians and patients regarding CT-CONT/DISC. Highlights: The efficacy of chemotherapy in the treatment of metastatic oesophageal squamous carcinoma has not been demonstrated so far. In this setting, chemotherapy until progression provides a 9-month survival rate that is similar to chemotherapy interruption. Chemotherapy until progression is associated with a numerically extended delay in the worsening of some symptoms.